A prospective study of efficacy and safety of mifepristone and vaginal misoprostol in termination of pregnancy up to 63 days of gestation - Jain, Mahima; Sharma, Sonali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Illegal abortion is still one of the important causes of maternal mortality in India accounting for approximately 13%. Medical Management of abortion is a non-surgical termination which does not require special facilities like operation theatre, hospital stay and thereby reduces complications associated with the same. Methods: It is a prospective study done in a Tertiary care Government Hospital over a span from Jan 2015 to April 2016. After patient selection as per inclusion criteria and written informed consent after evaluating patients were enrolled in the study. In first visit Tab. mifepristone 200 mg. orally was given and advised to take Tab. misoprostol 800 mcg. Vaginally after 48 hours at home. They were counselled for side effects and asked to report in case of excess bleeding, pain, fever or no bleed for 24 hours of misoprostol. After 7 days follow up was done to ensure completion of abortion. Any additional drugs required were noted. Contraceptive advice is also given during these visits. Results: In our study 60 cases were taken. Majority of women are between 20-29 years of age which is peak reproductive age. 61.1% women are of second parity. The success rate of medical methods is 96.6%, two cases out of 60 underwent surgical evacuation and one was lost to follow up. Most common adverse effect noted is abdominal cramps. No patient required hospitalization. Additional Misoprostol was required in 4 cases. This method is highly acceptable 95% cases as it is non invasive and preferred to adopt the same in future if needed. Conclusions: Patient participation, motivation, compliance, regular follow up visits, ability to record and report complications are the pillars on which the success of medical methods depends. Hence overall, it came out to be safe and effective method.